Cardiovascular Morbidity and Mortality in Men – Findings from a Meta-analysis on the Time-related Measure of Risk of Exogenous Testosterone. Issue 8 (23rd June 2022) - Fallara, Giuseppe; Pozzi, Edoardo; Belladelli, Federico; Corsini, Christian; Boeri, Luca; Capogrosso, Paolo; Montorsi, Francesco; Salonia, Andrea
ABSTRACT: Background: In the context of established male hypogonadism, testosterone therapy (TTh) has been employed to regain physiologic levels of circulating testosterone and improve sexual function and overall quality of life. Aim: To assess the risk of cardiovascular disease and mortality as time-dependent outcomes in treated vs TTh untreated hypogonadal men. Methods: A meta-analysis using weighted time-related measure of risk (hazard ratios (HRs)) for each of the outcome for all included studies was performed. Studies investigating male adults (≥18 years old) diagnosed with hypogonadism and divided into 2 arms (a treatment arm [any TTh] and a control arm [observation or placebo]) and assessing the risk of death and/or cardiovascular events were included. Single arm, non–comparative studies were excluded as well as studies that did not report the HRs for the chosen outcomes. This systemic review was registered on PROSPERO (CRD42022301592) and performed according to MOOSE and PRISMA guidelines. Outcomes: Overall mortality and cardiovascular events of any type. Results: Overall, 10 studies were included in the meta-analysis, involving 179, 631 hypogonadal men. Hypogonadal men treated with TTh were found to be at lower mortality risk from all causes relative to the control (observation or palcebo) arm (HR: 0.70; 95% Confidence Interval [CI]: 0.54–0.90; P < . 01), whilst any unfavorable effect of TTh in hypogonadal men in terms of cardiovascular events compared to untreated/observed hypogonadal men was found (HR: 0.98; 95% CI 0.73–1.33; P = . 89). Clinical implications: TTh in hypogonadal men might play a role in reducing the overall risk of death without increasing cardiovascular events risk. Strengths & Limitation: Main limitations are represented by the high heterogeneity among the studies in terms of included population, definition for hypogonadism, type of TTh, definition of cardio-vascular event used, and the length of follow-up. Conclusion: According to time-related measures of risk only, an increased risk of long-term morbidity and early mortality for untreated hypogonadal men was depicted, further outlining the clinical importance and safety of TTh in true hypogonadal men, with the urgent need of collecting long-term follow-up data.